[quotation] 'Losing ground - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'Losing ground poses a threat to a country s capacity to feed itself in the future. It presents a challenge to governments to come up with a comprehensive, valuable programme of public awareness. We need guidelines that even a young person can...